Workshop IT Metode Pembelajaran Online dengan Animaker - Besus Maulana Sulthon; Eko Setia Budi; Eva Zuraedah; Ade Priyatna; Sanwani Sanwani; Zakaria Maulana Arif; Dina Faisha; Ratih Kumala Sari; Muhammad Sudiyanto; Achmad Faisal (Journal of Social Responsibility Projects by Higher Education Forum, 2021)
PKK in Kelurahan Kebon Bawang is a community organization that functions as a facilitator, planner, implementer, controller and activator at each level for the implementation of the PKK program. The relationship between the mobilizing teams is consultative and coordinative by still paying attention to the hierarchy of functions of the PKK movement in DKI Jakarta Province. The relationship between the Kebon Bawang Urban Village PKK Driving Team and the Kelurahan PKK Driving Team chaired by the Kebon Bawang Urban Village is consultative and coordinative. Limitations in using the animaker program as a supporting tool in making teaching materials / material that can be conveyed online, therefore the Nusa Mandiri College of Information and Computer Management carries out Community Service in the form of IT Workshop Training for Online Learning Methods with Animakers at PKK in Kebon Village Onions in North Jakarta. With this training, it can help individuals in PKK in Kebon Bawang Village in making tools as a means of making materials for online learning during the pandemic.